2013
DOI: 10.1371/journal.pone.0076556
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Slowing and Upregulation of Inhibition in Cortex Are Correlated with Behavioral Deficits in Protein Malnourished Rats

Abstract: Protein malnutrition during early development has been correlated with cognitive and learning disabilities in children, but the neuronal deficits caused by long-term protein deficiency are not well understood. We exposed rats from gestation up to adulthood to a protein-deficient (PD) diet, to emulate chronic protein malnutrition in humans. The offspring exhibited significantly impaired performance on the ‘Gap-crossing’ (GC) task after reaching maturity, a behavior that has been shown to depend on normal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 84 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…Numerous studies have attempted to elucidate the impact of the insults occurring in development and early life (Chaudhary et al, 2013; da Silva et al, 2013; Dyer and Rosenfeld, 2011). In this sense, there is thought to be a strong relationship between an inadequate diet, imbalanced neurotransmission, and important neurological disorders (Chaudhary et al, 2013). The results of the present investigation demonstrate that exposure to low protein diet during gestation and lactation can affect feeding behaviours in adult female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have attempted to elucidate the impact of the insults occurring in development and early life (Chaudhary et al, 2013; da Silva et al, 2013; Dyer and Rosenfeld, 2011). In this sense, there is thought to be a strong relationship between an inadequate diet, imbalanced neurotransmission, and important neurological disorders (Chaudhary et al, 2013). The results of the present investigation demonstrate that exposure to low protein diet during gestation and lactation can affect feeding behaviours in adult female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to elucidate the impact of the insults occurring in development and early life (Chaudhary et al, 2013;Dyer and Rosenfeld, 2011). In this sense, there is thought to be a strong relationship between an inadequate diet, imbalanced neurotransmission, and important neurological disorders (Chaudhary et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of infection, protein-energy malnutrition has an adverse effect on behavior compared with nutrient sufficiency in rats. 114,115 Additional studies show that behaviors of undernourished dams and their offspring are negatively impacted, 115,116 linking diet and microbiota (by proxy) to brain function. Metabolism of food by the host (and perhaps by the mother) has the potential to affect host genetics.…”
Section: Environmental Enteropathy and Genetic Predispositionmentioning
confidence: 99%
“…In addition to possible deleterious health consequences, early malnutrition or undernutrition is known to cause impaired cognitive functions in infants, with long‐term effects in adulthood (Al‐Harbi et al, 2017; Pérez‐García et al, 2016; Peter et al, 2016). Studies in both rodents and humans have demonstrated that several cognitive deficits are produced by perinatal food restriction, including deficient attentional performance, emotional reactivity, and short and long‐term memory processes (Chaudhary et al, 2013; McGaughy et al, 2014; Rotta et al, 2008). Undernutrition also plays a critical role in the consolidation of certain types of memories, although the brain mechanisms involved are not fully understood.…”
Section: Introductionmentioning
confidence: 99%